Enhancing Repurchase Intention Through Customer Satisfaction: the Role of Brand Image and After-Sales Service - Jannah, Nurul; Muryati; Survival (Bulletin of Management and Business, 2024)
The skincare industry in Indonesia has experienced rapid growth, marked by increased competition among local and global brands. This study investigates the influence of brand image and after-sales service on repurchase intention, with customer satisfaction as a mediating variable. Using a quantitative explanatory approach, data were collected through questionnaires from 220 consumers of DDBeauty skincare products by PT. Kiara BeautyMed. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 3.0. The results indicate that both brand image and after-sales service significantly influence customer satisfaction but do not directly impact repurchase intention. Customer satisfaction, however, has a strong and significant effect on repurchase intention and fully mediates the relationships between brand image and repurchase intention, as well as between after-sales service and repurchase intention. The coefficient of determination (R²) reveals that the model explains 93.5% of the variance in customer satisfaction and 89.2% in repurchase intention. These findings highlight the critical role of satisfaction as a psychological bridge connecting brand perception and service quality with actual buying behavior. The study contributes to marketing theory by validating the mediating effect of satisfaction and offers practical insights for skincare companies to strengthen branding and service strategies to foster consumer loyalty.